Improving The Efficiency Of Air Filters In Dusty Environments - Abdiqodirov Shavkat Abdixamidovoch; Abduqahorov No‘monbek Oybek o‘g‘li (Periodica Journal, 2025)
This scientific article examines the issue of improving the efficiency of air filters in vehicles operating under dusty climate and road conditions. The impact of dust and fine particles in the intake air on engine power, fuel consumption, and maintenance intervals was analyzed. Practical recommendations for optimizing air filter design were developed based on the local dust composition, particle size, and density. The effects of filter element material, layer thickness, and filtration surface geometry on efficiency were investigated through experimental results.
Keywords: air filter; dust; engine; filtration efficiency